Factors Influencing Death Anxiety: A Systematic Review: A Systematic Literature Review - Nur Aziza Ilmi; Iswinarti Iswinarti (International Journal Labs, 2026)
Death anxiety is a feeling of fear and worry that arises when individuals contemplate their own death or the death of others. This systematic review aims to identify factors associated with death anxiety based on current scientific literature. Through a rigorous selection process following PRISMA guidelines, 11 international journal articles published during 2019–2025 were selected for analysis. The results demonstrate that internal psychological factors, particularly meaning in life and self-esteem, are the primary determinants in mitigating death anxiety. Social factors such as loneliness and low family emotional attachment emerge as significant risk factors. Furthermore, spiritual health, mindfulness coping strategies, and demographic characteristics also influence the level of death anxiety. The analysis reveals that self-esteem functions as a